Tatbiiqu Tooriqoti al-Qiroah al-Jahriyah Lii Tarqiyati Aswat al-Arabiyah - Muh Dimyati; Choirotun Niswah (Institut Agama Islam Darusssalam Blokagung, 2021)
The method in a learning has a very important role. Because through the learning method it can run smoothly. Likewise, learning qira'ah. In the implementation of qira'ah learning, it will not be separated from recognizing the hijyaiyyah letters and how to sound and place the letters correctly so that the qira'ah learning can be conveyed properly. This research is a qualitative descriptive study using the field research method. In collecting data, researchers used several methods including observation, interviews, tests, and documentation. The results of this study indicate that the implementation of qira'ah jahriyyah in the classroom uses three methods and each method has its own purpose. This is so that qira'ah learning can improve students' abilities in saying makhraj and the sound of lafadz or Arabic sentences. From the test results, it was stated that the majority of students had mastered the pronunciation of Arabic lafadz sounds and only a small portion needed more practice in reading Arabic sentences in order to hone ashwat arabiyyah. Thus the jahriyyah method is considered effective and able to improve student fluency in speaking makhraj and Arabic sound and increase student confidence.